Follicular Development in Ewes During Natural and Prostaglandins Induced Estrous Cycle - Fernando Uribe-Velasquez, Luis; Oba, Eunice [UNESP]; Lenz Souza, Maria Ines; Velez-Marin, Miryam; Correa-Orozco, Adriana (Univ Zulia, Facultad Ciencias Veterinarias, 2010)
The follicular development was evaluated in ovine females during natural and prostaglandin-F(2 alpha) (PG) induced estrous cycle. Ewes were randomly divided in two treatments (n=7/treatment): T1 with natural cycle and T2 synchronized with two injections of PG. From one day before PG injection until next ovulation, daily transrectal ultrasonography was done. All follicles >= 2 mm were assessed. During the interovulatory intervals, follicular growth and regression occurred in a wave like pattern (2-3 waves). The maximum diameter of the largest follicle of the first wave was greater in T1 (5.83 +/- 0.31 mm) compared with T2 (5.0 +/- 0.1 mm; P<0.01), but there was no significant difference among the emergency day of largest follicle, during the growth phase of the follicular waves. The duration of the plateau phase in wave 2 differed between the two treatments (P<0.05) showing 0.83 +/- 0.31 and 1.83 +/- 0.17 d, for natural and synchronized treatment, respectively. Growth rate did not differ between treatments. Presence of new luteal tissue was detected on day 3 after ovulation. In conclusion, the follicular development was similar in female ovine during natural and PG induced estrous cycle.
Keywords: Follicles; estrous; prostaglandins; synchronization